Berberine Alleviates Insulin Resistance and Inflammation via Inhibiting the LTB4–BLT1 Axis - Gong, Minmin; Duan, Huiyan; Wu, Fan; Ren, Yanlin; Gong, Jing; Xu, Lijun; Lu, Fuer; Wang, Dingkun (Frontiers in Pharmacology, 2021)
Background: Chronic low-grade inflammation is recognized as a key pathophysiological mechanism of insulin resistance. Leukotriene B4 (LTB4), a molecule derived from arachidonic acid, is a potent neutrophil chemoattractant. The excessive amount of LTB4 that is combined with its receptor BLT1 can cause chronic low-grade inflammation, aggravating insulin resistance. Berberine (BBR) has been shown to relieve insulin resistance due to its anti-inflammatory properties. However, it is not clear whether BBR could have any effects on the LTB4-BLT1 axis. Methods: Using LTB4 to induce Raw264.7 and HepG2 cells, we investigated the effect of BBR on LTB4-BLT1 axis in the progression of inflammation and insulin resistance. Results: Upon exposure to LTB4, intracellular insulin resistance and inflammation increased in HepG2 cells, and chemotaxis and inflammation response increased in RAW264.7 cells. Interestingly, pretreatment with BBR partially blocked these changes. Our preliminary data show that BBR might act on BLT1, modulating the LTB4-BLT1 axis to alleviate insulin resistance and inflammation. Conclusions: Our study demonstrated that BBR treatment could reduce intracellular insulin resistance and inflammation of hepatic cells, as well as chemotaxis of macrophages induced by LTB4. BBR might interact with BLT1 and alter LTB4-BLT1 signaling pathway. This mechanism might be a novel anti-inflammatory and anti-diabetic function of BBR. Keywords: Leukotriene B4; Insulin resistance; Inflammation; Berberine; Diabetes